Is central obesity associated with diabetic retinopathy in Chinese individuals? An exploratory study. Issue 11 (November 2019) - Zhou, Jian-Bo; Yuan, Jing; Tang, Xing-Yao; Zhao, Wei; Luo, Fu-Qiang; Bai, Lu; Li, Bei; Cong, Jia; Qi, Lu; Yang, Jin-Kui
Objective: To our knowledge, the independent association between central obesity, defined by waist circumference (WC) or waist-to-hip ratio (WHR), and diabetic retinopathy (DR) remains unknown in Chinese individuals. Method: The study was conducted in two stages. First, the relationship between WC or WHR and DR was estimated in a case-control set (DR vs. non-DR) for the whole population before and after propensity score matching. Subsequently, a systematic review and meta-analysis was performed on evidence from the literature to validate the relationship. Results: Of 511 eligible patients, DR (N = 156) and non-DR (N = 156) patients with similar propensity scores were included in the propensity score matching analyses. Central obesity (defined by WC) was associated with risk of DR (odds ratio [OR] 1.07, 95% confidence interval [95% CI] (1.03–1.10). The meta-analysis showed that central obesity significantly increased the risk of DR by 12% (OR 1.12, 95% CI 1.02–1.22). Analysis of data from 18 studies showed a significant association between continuous body mass index and risk of proliferative DR (OR 0.95, 95% CI 0.93–0.98; I 2 = 50%). Conclusion: Central obesity, particularly as defined by WC, is associated with the risk of DR in the Chinese population.